Intelligent real-time pressure tracking system using a novel hybrid control scheme. (September 2018) - Lin, Zhonglin; Zhang, Tianhong; Xie, Qi
In this paper, a novel hybrid control scheme is proposed to improve the control performance in a real-time pressure tracking system using fast on-off solenoid valves. In this novel hybrid control scheme, an original approach named Time Interlaced Modulation (TIM) is developed to replace the traditional Pulse Width Modulation (PWM) approach. Besides using TIM, a new switching method which is referred as seven possible control modes is designed to ensure the proper switching states of the valves. Moreover, a controller with field programmable gate array (FPGA) is chosen to guarantee the real-time implementation of the control algorithm. All the simulations and experimental results implemented on FPGA verify the feasibility of the hybrid control scheme.